PENGARUH KEPRIBADIAN PROAKTIF TERHADAP KEPUASAN KARIR DAN KINERJA KARYAWAN DENGAN KREATIVITAS KARYAWAN SEBAGAI VARIABEL INTERVENING - Miranti Sukmajati; Suharnomo Suharnomo (JURNAL STUDI MANAJEMEN ORGANISASI, 2020)
This study aims to analyze the effect of proactive pesonality on career satisfaction and employee performance by employee creativity as intervening variables. This Study uses two types of data sources, namely primary data in the form of interviews with respondents and quetionaire results via Google Form Link, while secondary data is obtaining from primary data processing using Stuctural Equation Model (SEM) as a data analysis tool consisting of 5 (five) hypothesis which is then operated using the AMOS computational program. In this study, data were obtained from respondents, namely Bank BTN Semarang City employees with 110 respondents.The results show that proactive personality have a positive and significant effect on employee creativity, employee creativity have a positive and significant effect on career satisfaction, employee creativity have a positive and significant effect on employee performance, proactive personality have a positive and significant effect on career satisfaction, and proactive personality have a positive and significant effect on employee performance.